Who is a "real woman"? Empowerment and the discourse of respectability in Namibia's Zambezi region. (January 2015) - Khumalo, Kathryn E.; McKay, Kimber Haddix; Freimund, Wayne
Synopsis: The third Millennium Development Goal expresses a commitment to promoting gender equality and women's empowerment. We use respectability discourse as a lens for understanding constraints and opportunities for women's empowerment. A case study of Kwandu Conservancy, located in Namibia's Zambezi region, generated 49 interviews with women. We also collected data through participant observation, document review, and twenty key informant interviews. Our analysis revealed that a "real woman" construct embodies feminine respectability in Kwandu. While the construct reinforces a woman's power to provide a livelihood through educational achievement, hard work, and collaboration with supportive community members, spouses, and children, its narrow definition of respectability also disempowers. Fear of losing respect and access to resources restrict strategic choices like choosing to divorce or remain single, saving rather than sharing resources, valuing and pursuing informal knowledge, and directly challenging limitations, uncertainties, and inequalities that can deter women from achieving a 'better life'.